Learn more about

Refine search

Results (displaying matches 1-50 of 595) Next

Label Class Equation Sato-Tate \(\overline{\Q}\)-simple \(\GL_2\) Rank*
448.a.448.1 448.a \(y^2 + (x^3 + x)y = x^4 - 7\) $N(G_{1,3})$ 0
644.a.2576.1 644.a \(y^2 + (x^2 + x)y = -5x^6 + 11x^5 - 20x^4 + 20x^3 - 20x^2 + 11x - 5\) $G_{3,3}$ 0
686.a.686.1 686.a \(y^2 + (x^2 + x)y = x^5 + x^4 + 2x^3 + x^2 + x\) $N(G_{1,3})$ 0
784.b.76832.1 784.b \(y^2 + (x + 1)y = -x^6 + 4x^5 - 4x^4 - 2x^3 + 10x - 9\) $G_{3,3}$ 0
816.b.52224.1 816.b \(y^2 + (x^3 + x)y = -x^6 - 12x^4 - 27x^2 - 17\) $G_{3,3}$ 0
1038.a.1038.2 1038.a \(y^2 + (x^3 + 1)y = x^4 + 2x^2 + x + 1\) $\mathrm{USp}(4)$ 0
1038.a.1038.1 1038.a \(y^2 + (x^2 + x)y = x^5 - 12x^4 + 26x^3 + 46x^2 + 21x + 3\) $\mathrm{USp}(4)$ 0
1055.a.1055.1 1055.a \(y^2 + (x^3 + 1)y = -x^4 + x^2 - x - 1\) $\mathrm{USp}(4)$ 0
1088.a.1088.1 1088.a \(y^2 + (x^3 + x^2 + x + 1)y = x^4 + x^3 + 2x^2 + x + 1\) $N(G_{3,3})$ 0
1088.b.2176.1 1088.b \(y^2 + (x^3 + x)y = 4x^4 + 24x^2 + 34\) $N(G_{1,3})$ 0
1137.a.1137.1 1137.a \(y^2 + (x^2 + x + 1)y = x^5 + x^4 + x^3\) $\mathrm{USp}(4)$ 0
1146.a.2292.1 1146.a \(y^2 + xy = x^5 + 3x^4 + 5x^3 + 4x^2 + 2x\) $\mathrm{USp}(4)$ 0
1216.a.1216.1 1216.a \(y^2 + (x + 1)y = -x^6 + x^4 - x^3 - x^2\) $\mathrm{USp}(4)$ 0
1239.a.8673.1 1239.a \(y^2 + (x^2 + x + 1)y = -x^6 - x^2 - x\) $\mathrm{USp}(4)$ 0
1270.a.1270.1 1270.a \(y^2 + (x^3 + 1)y = -2x^4 + 5x^2 - 2x - 3\) $\mathrm{USp}(4)$ 0
1300.a.130000.1 1300.a \(y^2 + (x^3 + x)y = 2x^4 + 9x^2 + 13\) $G_{3,3}$ 1
1376.b.176128.1 1376.b \(y^2 + y = 4x^5 + 4x^4 + x^3 + 2x^2\) $\mathrm{USp}(4)$ 0
1408.a.180224.1 1408.a \(y^2 + (x^3 + x^2 + x + 1)y = x^4 - x^3 - 5x + 1\) $\mathrm{USp}(4)$ 0
1460.a.5840.1 1460.a \(y^2 + (x^3 + x)y = x^6 + 14x^4 + 56x^2 + 73\) $G_{3,3}$ 0
1473.a.1473.1 1473.a \(y^2 + (x^2 + x + 1)y = x^5 - x^4 - x\) $\mathrm{USp}(4)$ 0
1564.a.50048.1 1564.a \(y^2 + (x^3 + 1)y = -x^6 + 7x^5 + 8x^4 + 17x^3 + 8x^2 + 7x - 1\) $G_{3,3}$ 0
1568.a.1568.1 1568.a \(y^2 + (x^3 + x)y = x^4 + 3x^2 + 2\) $G_{3,3}$ 0
1568.a.43904.1 1568.a \(y^2 + (x^3 + x)y = -5x^4 + 27x^2 - 56\) $G_{3,3}$ 0
1568.b.12544.1 1568.b \(y^2 + (x^3 + x)y = -x^4 + 1\) $G_{3,3}$ 1
1600.a.409600.1 1600.a \(y^2 = x^6 - 2x^2 - 1\) $G_{3,3}$ 0
1649.a.159953.1 1649.a \(y^2 + (x^3 + x^2 + x)y = x^4 + 3x^3 + 4x^2 + 6x + 5\) $\mathrm{USp}(4)$ 0
1695.a.1695.1 1695.a \(y^2 + (x^3 + 1)y = x^5 + x^4 + x^2 - 1\) $\mathrm{USp}(4)$ 0
1712.a.109568.1 1712.a \(y^2 + (x^2 + 1)y = x^5 + 6x^4 + 4x^3 + 9x^2 + 3x\) $\mathrm{USp}(4)$ 0
1728.b.442368.1 1728.b \(y^2 = x^6 + 4x^4 + 6x^2 + 3\) $N(G_{1,3})$ 0
1743.a.597849.1 1743.a \(y^2 + (x^2 + x + 1)y = 3x^6 + 2x^5 + 3x^4 + 3x^3 - x^2 + x - 1\) $\mathrm{USp}(4)$ 0
1744.a.1744.1 1744.a \(y^2 + (x^3 + x)y = x^3 + x\) $\mathrm{USp}(4)$ 0
1780.a.7120.1 1780.a \(y^2 + (x^3 + x)y = x^6 - 16x^4 + 64x^2 - 89\) $G_{3,3}$ 0
1795.a.224375.1 1795.a \(y^2 + (x^3 + x^2 + x)y = -x^6 - 8x^4 + 3x^3 - 23x^2 + 6x - 23\) $\mathrm{USp}(4)$ 0
1798.a.3596.1 1798.a \(y^2 + (x^2 + x)y = x^5 + 4x^4 + 2x^3 + 4x^2 + x + 1\) $\mathrm{USp}(4)$ 0
1988.a.3976.1 1988.a \(y^2 + (x^2 + x)y = 6x^6 + 16x^5 + 31x^4 + 35x^3 + 31x^2 + 16x + 6\) $G_{3,3}$ 0
2028.a.64896.1 2028.a \(y^2 + (x^2 + x)y = x^6 + x^5 + 4x^4 + 6x^3 + 6x^2 + 9x + 5\) $G_{3,3}$ 0
2056.b.4112.1 2056.b \(y^2 + xy = 2x^5 - x^4 + 3x^3 - x^2 + x\) $\mathrm{USp}(4)$ 0
2106.a.711828.1 2106.a \(y^2 + (x^2 + 1)y = 2x^5 - 4x^4 + x^3 + x^2 - 1\) $\mathrm{USp}(4)$ 0
2112.a.33792.1 2112.a \(y^2 + y = 4x^5 + 6x^4 + 5x^3 + 3x^2 + x\) $\mathrm{USp}(4)$ 0
2156.a.17248.1 2156.a \(y^2 + (x^2 + x)y = 2x^5 + 5x^4 + 7x^3 + 5x^2 + 2x\) $G_{3,3}$ 0
2156.b.34496.1 2156.b \(y^2 + (x^2 + x)y = 2x^5 - x^4 - 5x^3 + 3x + 1\) $G_{3,3}$ 1
2166.b.123462.1 2166.b \(y^2 + (x^3 + x)y = -x^6 - x^5 + 5x^3 + 8x^2 + 7x + 3\) $G_{3,3}$ 0
2176.a.69632.2 2176.a \(y^2 + xy = x^6 + 9x^4 + 24x^2 + 17\) $N(G_{1,3})$ 0
2178.b.176418.1 2178.b \(y^2 + (x^2 + x)y = x^5 - x^4 - 3x^3 - x^2 + x\) $G_{3,3}$ 0
2187.a.6561.1 2187.a \(y^2 + (x^3 + 1)y = -1\) $J(E_3)$ 0
2192.a.4384.1 2192.a \(y^2 + (x^3 + x)y = -x^4 - x^3 - 2x^2 - x - 1\) $\mathrm{USp}(4)$ 0
2214.a.816966.1 2214.a \(y^2 + (x + 1)y = x^5 + 3x^4 - 56x^3 + 27x^2 - 5x\) $\mathrm{USp}(4)$ 1
2298.a.20682.1 2298.a \(y^2 + xy = x^5 + 12x^4 + 40x^3 - 111x + 63\) $\mathrm{USp}(4)$ 0
2300.a.4600.1 2300.a \(y^2 + (x^2 + x)y = x^5 + 3x^4 - 6x^3 + 6x^2 - 3x + 1\) $\mathrm{USp}(4)$ 0
2320.a.11600.1 2320.a \(y^2 + (x + 1)y = -x^6\) $\mathrm{USp}(4)$ 0
Next

Download all search results for